Combined modality treatment for malignant pleural mesothelioma: a single-centre long-term survival analysis using extrapleural pneumonectomy. (6th December 2018) - Frick, Anna Elisabeth; Nackaerts, Kristiaan; Moons, Johnny; Lievens, Yolande; Verbeken, Eric; Lambrecht, Maarten; Coolen, Johan; Dooms, Christophe; Vansteenkiste, Johan; De Leyn, Paul; Nafteux, Philippe
Abstract: OBJECTIVES: Combined modality treatment (CMT) for malignant pleural mesothelioma (MPM) remains a matter of debate regarding the choice of surgical procedure: extrapleural pneumonectomy (EPP) or pleurectomy/decortication. METHODS: We performed a prospective interventional cohort study between 2003 and 2014. All consecutive patients with any histological MPM subtype, ≤70 years old, World Health Organization performance status ≤1, medically fit for pneumonectomy and stage cT1-2cN0-2cM0 (TNM7) or lower were included. Eligibility for CMT was discussed by the multidisciplinary tumour board. Our local CMT protocol consisted of induction chemotherapy, followed by EPP and hemithoracic radiotherapy. Induction chemotherapy consisted of 3 cycles of cisplatin (75 mg/m 2 day 1) and pemetrexed (500 mg/m 2 day 1), each administered once every 3 weeks. If non-progressive, EPP was performed followed by hemithoracic radiotherapy (most frequently, intensity-modulated radiotherapy; dose 54 Gy/1.8 Gy ± boost). Feasibility and long-term survival analyses were performed. Overall survival and disease-free survival (DFS) were calculated from histological confirmation of a diagnosis of MPM. RESULTS: Out of 197 patients, 97 started with CMT (79 epithelioid, 15 mixed and 3 sarcomatoid tumours, based on histological analysis). Clinical TNM was IA ( n = 9)/IB ( n = 8)/II ( n = 57)/III ( n = 23). A total of 76 patients underwent surgery (EPP: n = 56; exploratory thoracotomy: n = 20). The in-hospital mortality rate was 3.6%. Out of 56 patients who underwent surgery, 47 completed the entire CMT protocol. The intent-to-treat median and 5-year OS were 22.4 [95% confidence interval (CI) = 15.5–27.9] months and 11.2% (95% CI = 6.9–23.4). In patients who completed the CMT protocol ( n = 47), these values were 33.2 (95% CI = 23.0–45.0) months and 24.2% (95% CI = 13.4–43.8). The intent-to-treat median and 5-year DFS were 15.6 (95% CI = 14.0–17.3) months and 9.9% (95% CI = 5.1–19.2), 19.8 (95% CI = 16.8–27.7) months and 17.2% (95% CI = 8.6–34.1) in those who had the full CMT. The Cox proportional hazards model showed a significantly lower DFS in positive lymph nodes (HR 2.79, 95% CI=1.35-5.78; P =0.006). In 30 (64%) patients with epithelioid type MPM without positive lymph nodes (pN0) after EPP, the 5-year DFS was 27.0% (95% CI=14.1-51.7). CONCLUSIONS: CMT with EPP for MPM is feasible, with an acceptable surgical mortality rate, and results in a 5-year survival rate of 24%. Careful patient selection (staging and physical performance) is extremely important.